2016
DOI: 10.21082/jpptp.v35n3.2016.p199-208
|View full text |Cite
|
Sign up to set email alerts
|

Keragaman Genetik dan Penampilan Jagung Hibrida Silang Puncak pada Kondisi Cekaman Kekeringan

Abstract: Maize breeding population with a wide genetic diversity is required to develop superior drought tolerant varieties. The objective of this research was to obtain information on genetic diversity, heritability value and grain yield performance, yield components and agronomic traits of maize genotypes derived from top cross under severe drought stress. One hundred and fifty maize genotypes derived from top cross and four hybrids maize as check varieties, were tested in Probolinggo, East Java, and Gowa, South Sula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
0
9
0
2
Order By: Relevance
“…Several researchers have studied heritability in maize. Wannows, et al (2010);Shahrokhi, et al (2013); Azrai, et al (2016); Kandel et al (2018); Lubis, et al (2014) found that the character of ASI (Anthesis Silk Interval), cob dry weight, seed dry weight, and cob weight/plot had broad genetic diversity values, followed by high heritability. Traits that have wide genetic diversity and high heritability can be selected directly.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have studied heritability in maize. Wannows, et al (2010);Shahrokhi, et al (2013); Azrai, et al (2016); Kandel et al (2018); Lubis, et al (2014) found that the character of ASI (Anthesis Silk Interval), cob dry weight, seed dry weight, and cob weight/plot had broad genetic diversity values, followed by high heritability. Traits that have wide genetic diversity and high heritability can be selected directly.…”
Section: Introductionmentioning
confidence: 99%
“…Narrow genetic diversity indicates that subsequent selection for this trait will not be effective (Rachman et al 2022). Azrai et al (2016) reported the same result that the genetic diversity of harvest cob weight was narrow with a genetic diversity value of 0.11 and a CGD value of 7.751%. However, Lubis et al (2014) found the opposite the genetic diversity of cob dry weight was high in acid soil.…”
Section: Discussionmentioning
confidence: 85%
“…The breadth or narrowness of the genetic diversity of a trait was obtained from the Coefficient of Genetic Diversity (CGD) value category, using the formula developed by Azrai et al (2016) as follows:…”
Section: P0 Initial Population P1ismentioning
confidence: 99%
See 2 more Smart Citations